2004
DOI: 10.1097/00006324-200407000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Using the Freiburg Acuity and Contrast Test to Measure Visual Performance in USAF Personnel After PRK

Abstract: PRK does not appear to have affected VA, but the changes in CS might represent a true decline in visual performance. The greater disruptive effects from laser versus broadband glare may be a result of increased masking from coherent spatial noise (speckle) surrounding the laser stimulus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…This trend was observed in other results from the comprehensive PRK Study as well (26,67,68). However, an opposite trend was found in controls.…”
Section: Analysis Of Nvg Visual Acuity Datasupporting
confidence: 80%
See 1 more Smart Citation
“…This trend was observed in other results from the comprehensive PRK Study as well (26,67,68). However, an opposite trend was found in controls.…”
Section: Analysis Of Nvg Visual Acuity Datasupporting
confidence: 80%
“…Accordingly, the job of the Aerospace Ophthalmology Branch at the USAF School of Aerospace Medicine is to be a sentinel for aviators and ensure that nothing is done that might degrade vision or ultimately affect flying performance. This study, which was part of the larger USAF comprehensive PRK study (26,68), was specifically designed to expose any negative effects on night mesopic and NVG visual performance.…”
Section: Discussionmentioning
confidence: 99%
“…This value represents the reciprocal of the CS. The logarithm of CS values was used for later statistical analysis (Bu¨hren et al 2006;Dennis et al 2004;Patel et al 2009). …”
Section: Contrast Sensitivitymentioning
confidence: 99%
“…Unlike several recent studies that measured visual performance of refractive surgery subjects with their most recent spectacle refraction [Schlote et al, 1999;MontesMico et al, 2003;Bailey et al, 2004;Dennis et al, 2004;Quesnel et al, 2004], we elected not to refract any of the subjects so that they may not have had their optimal acuity even though they had an acuity of at least 0.0 logMAR (i.e., 6/ 6 or 20/20). It was anticipated that the vast majority of subjects would have a visual acuity of 0.0 logMAR, or better, as they had been recently screened prior to enrolling in the College.…”
Section: Discussionmentioning
confidence: 99%
“…The contrast sensitivity loss extended to the medium and low spatial frequencies for the PRK subjects [Montes-Mico and Charman, 2002]. Dennis et al [2004] reported reductions in photopic contrast sensitivity with, and without, glare 2 years after surgery.Policing is one occupation that is visually demanding and the duties are carried out in adverse viewing conditions. Adequate vision at night is often cited by subject matter experts as being an essential requirement for policing [Shaw and Gledhill, 1995].…”
mentioning
confidence: 99%